2012
DOI: 10.1179/1362171812y.0000000022
|View full text |Cite
|
Sign up to set email alerts
|

Major factor causing improvement in fatigue strength of butt welded steel joints after laser peening without coating

Abstract: Laser peening without coating (LPwC) can introduce compressive residual stress to the surface and, therefore, is effective in enhancing the fatigue strength. This study used butt welded structural steel joints to investigate changes in the residual stress and the hardness near the toe of the welded zone and to examine the major factor causing the improved fatigue strength due to LPwC. It is concluded that the generation of compressive residual stress by LPwC is the major factor improving the fatigue strength, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…Although fatigue-test conditions such as a load ratio and tensile strengths of structural steel plates investigated are different, the significant increase of the number of cycles to failure was not observed in this study, but it was obtained by further refinement in the fine-grained FSP region (not shown here). The laser peening provided increase of Vickers hardness due to work hardening in the region from immediately beneath to 0.2 mm below the surface and large compressive residual stress (about 400 MPa) in the region from immediately beneath to 1.0 mm below the surface [12]. The shot peening also provided large compressive residual stress (about 400 MPa around the surface) in the region from immediately beneath to 0.6 mm below the surface [13].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although fatigue-test conditions such as a load ratio and tensile strengths of structural steel plates investigated are different, the significant increase of the number of cycles to failure was not observed in this study, but it was obtained by further refinement in the fine-grained FSP region (not shown here). The laser peening provided increase of Vickers hardness due to work hardening in the region from immediately beneath to 0.2 mm below the surface and large compressive residual stress (about 400 MPa) in the region from immediately beneath to 1.0 mm below the surface [12]. The shot peening also provided large compressive residual stress (about 400 MPa around the surface) in the region from immediately beneath to 0.6 mm below the surface [13].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, residual tensile stress would be produced in the TIG weld beads, and thus the weld part would be a weak point in the structure. Peening techniques such as laser peening [12] were performed to convert tensile stress remaining in the weld beads to compressive stress. Thus, to understand the effect of FSP on the residual tensile stress in the TIG weld beads, residual stress was measured for the TIG-welded steel specimens with and without FSP, and the results are shown in Figure 8, together with those for steel specimens only with FSP for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, they also studied changes in the surface residual stress, the depth distribution of residual stress, the hardness distribution, and the surface roughness in four types of structural steel with different strengths and in the welded zone 9) . Moreover, it is clarified that the fatigue life of the welded joints is substantially extended by laser peening 10 11) and the generation of compressive residual stress by laser peening is the major factor improving the fatigue life 12) .…”
Section: Introductionmentioning
confidence: 99%